2021
DOI: 10.1016/j.ebiom.2020.103203
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and predicted neutralisation coverage of VRC01 in HIV-uninfected participants of the Antibody Mediated Prevention (AMP) trials

Abstract: The phase 2b AMP trials are testing whether the broadly neutralising antibody VRC01 prevents HIV-1 infection in two cohorts: women in sub-Saharan Africa, and men and transgender persons who have sex with men (MSM/TG) in the Americas and Switzerland. We used nonlinear mixed effects modelling of longitudinal serum VRC01 concentrations to characterise pharmacokinetics and predict HIV-1 neutralisation coverage. We found that body weight significantly influenced clearance, and that the mean peripheral volume of dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…, Eq 1 a relationship that has been empirically confirmed for single bNAbs 19,20 . As a potency measure, titer expresses the fold-relationship between concentration and viral IC50 as a measure of 'protection' against that virus.…”
Section: Fig 1 Pkpd Model Schematic For Optimizing Combination Treatment Against a Genetically Diversementioning
confidence: 76%
See 1 more Smart Citation
“…, Eq 1 a relationship that has been empirically confirmed for single bNAbs 19,20 . As a potency measure, titer expresses the fold-relationship between concentration and viral IC50 as a measure of 'protection' against that virus.…”
Section: Fig 1 Pkpd Model Schematic For Optimizing Combination Treatment Against a Genetically Diversementioning
confidence: 76%
“…We previously integrated pharmacokinetic (PK) and multi-strain pharmacodynamic (PD) models to determine longitudinally varying potency of VRC01, a broadly neutralizing antibody (bNAb), to simulate prevention trials and predict strain coverage 18,19 . Because of HIV genetic diversity, it is essential to consider the distribution of potencies against the diverse population of viral strains.…”
Section: Fig 1 Pkpd Model Schematic For Optimizing Combination Treatment Against a Genetically Diversementioning
confidence: 99%
“…A key secondary endpoint was to determine if an association existed between serum neutralization activity and the ID 50 or ID 80 titers required for protection as had been shown in NHP/ SHIV models (41,110). Based on the NHP models, it was estimated that protection would be achieved at serum antibody concentrations 50-100-fold higher than the measured IC 50 of the challenge (infecting) virus (32).…”
Section: Amp Efficacy Trialsmentioning
confidence: 99%
“…The underlying hypothesis of the coordinated AMP trials was that passive transfer of an HIV-1 bnAb would be efficacious at preventing sexual transmission of HIV-1 in exposed individuals. A key secondary endpoint was to determine if an association existed between serum neutralization activity and the ID 50 or ID 80 titers required for protection as had been shown in NHP/SHIV models ( 41 , 110 ). Based on the NHP models, it was estimated that protection would be achieved at serum antibody concentrations 50-100-fold higher than the measured IC 50 of the challenge (infecting) virus ( 32 ).…”
Section: Clinical Evaluation Of Bnabsmentioning
confidence: 99%
“…The results of the first efficacy trials of an antibody for HIV prevention tested in Africa and the Americas have recently been published (14)(15)(16)(17). These two Antibody-Mediated Prevention (AMP www.ampstudy.org.za) trials showed that VRC01 had 75% prevention efficacy in high-risk men and women if the infecting virus was sensitive to the antibody at <1mg/ml (IC 80 ).…”
Section: Introductionmentioning
confidence: 99%